2015
DOI: 10.1038/mtm.2015.31
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of a heterologous prime-boost vaccination involving a truncated HER2 sequence in patients with HER2-expressing breast cancer

Abstract: A phase 1 clinical trial was conducted to assess the safety, tolerability, and preliminary efficacy of a heterologous prime-boost strategy involving plasmid DNA (pHM-GM-CSF, expressing truncated human epidermal growth factor receptor 2 (HER2) and granulocyte macrophage colony-stimulation factor (GM-CSF) as a bicistronic message) and an adenoviral vector (Ad-HM, containing the same modified HER2 sequence only), in patients with stage III–IV metastatic breast cancer expressing HER2. Nine eligible subjects were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…11 17 18 DNA prime followed by boosting with viral vectors has been used to enhance immune responses against malaria, 23 viruses, 24 25 and cancers. [26][27][28][29] Heterologous injections with plasmid-DNA vaccine followed by adenoviral (Ad5) vaccine, both encoding guanylyl cyclase C (GUCY2C), have been shown to effectively control CT26 tumor progression. 44 Similarly, a protocol consisting of priming with plasmid-DNA vaccine followed by boost injections with an adenoviral vaccine, both expressing a truncated human epidermal growth factor receptor 2 (HER2), has been shown to elicit Her-2/neu-specific humoral and cellular immune responses without causing severe adverse effects in monkeys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 17 18 DNA prime followed by boosting with viral vectors has been used to enhance immune responses against malaria, 23 viruses, 24 25 and cancers. [26][27][28][29] Heterologous injections with plasmid-DNA vaccine followed by adenoviral (Ad5) vaccine, both encoding guanylyl cyclase C (GUCY2C), have been shown to effectively control CT26 tumor progression. 44 Similarly, a protocol consisting of priming with plasmid-DNA vaccine followed by boost injections with an adenoviral vaccine, both expressing a truncated human epidermal growth factor receptor 2 (HER2), has been shown to elicit Her-2/neu-specific humoral and cellular immune responses without causing severe adverse effects in monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the preclinical data, HER2-specific cell-mediated and humoral responses was reported in some patients leading to objective responses without serious adverse events. 26 Based on our previous findings that heterologous prime/boost vaccination can enhance vaccine efficacy, 20 22 we cloned the TEM1 insert into a replication-deficient Ad5 adenoviral vector and then tested the novel vaccination protocol. We found that priming with the TEM1 plasmid-DNA followed by two boosts with TEM1 Ad5 bolstered the immune response against TEM1-specific peptides and improved DNA vaccine antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In many cases, a heterologous prime-boost administered with different types of vaccines containing the same antigens was more immunogenic than a homologous prime-boost that was repeatedly administered with the same type of vaccine. In combinations of heterologous prime-boost strategies, a DNA prime followed by boosting with viral vectors have enhanced immune responses to malaria, 36 viruses, 37,38 and cancers 25,26,39,40 .…”
Section: Introductionmentioning
confidence: 99%
“…DNA vaccines offer numerous advantages such as their capacity to readily incorporate multiple genes, their easy engineering and their stability [24]. Heterologous prime-boost strategies using a DNA prime followed by boosting with viral vectors have been shown to increase the magnitude of immune responses to HIV [25], Chikungunya virus [26], melanoma [27] or breast cancer [28]. Here, we have developed a recombinant MV vector expressing the insert of INVAC-1, which is a modified ubiquitin-hTERT fusion protein, as immunotherapeutic agent.…”
Section: Introductionmentioning
confidence: 99%